PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA APLIKASI MANAJEMEN LAUNDRY 1010DRY - Oji Setyawan; Wisnu Wibowo (FE Program Studi Manajemen, 2021)
Customer satisfaction is so important for service company because it would lead the customer to be loyal to the company. However, obtaining customer satisfaction is not easy because it needs a commitment from the company to provide the best quality service to satisfied the customer. At the beginning of the launch of 1010dry application by PT. Tenten Digital Indonesia, 1010dry has low rating and some reviews about issues on the application. PT. Tenten Digital Indonesia has been trying to solve the problem by improving their service both customer service and system maintenance untill the rating and the amount of new member each month has been increase. Therefore, the aim of this study is to examine the influence of quality service to customer satisfaction of 1010dry laundry management application. The method used in this research is quantitative method by using simple linear regression equation. Data was obtained from the member of 1010dry laundry management application by using questionnaire. The result of this research shows that quality service has significant influence to customer satisfaction (6,317 > 2,074 and 0,000 < 0,05) with coefficient of determination is 64,5%. Keywords: quality service and customer satisfaction.